2020
DOI: 10.1055/a-1192-5205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Resistance Exercise Orders on Muscular Function and Body Composition in Older Women

Abstract: The purpose of the present study was to compare the effects of three resistance exercise orders on muscular strength, body composition, and functional fitness in trained older women. Forty-five women (aged ≥60 years), after performing 12 weeks of a pre-conditioning resistance-training program were randomly assigned in one of the following groups that performed the exercises in the following orders: multi-joint t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 34 publications
2
23
1
Order By: Relevance
“…In a study that analyzed 45 women aged 60 years or older, it was observed that after a 12-week resistance training intervention, the older women showed an improvement in muscle strength and functional fitness tests [33], corroborating the findings of this study. Moreover, in another study that analyzed older women who participated in a multicomponent training program (upper and lower limbs), it was possible to see, after 56 weeks, improvements in functional autonomy, mobility, and flexibility [34].…”
Section: Discussionsupporting
confidence: 86%
“…In a study that analyzed 45 women aged 60 years or older, it was observed that after a 12-week resistance training intervention, the older women showed an improvement in muscle strength and functional fitness tests [33], corroborating the findings of this study. Moreover, in another study that analyzed older women who participated in a multicomponent training program (upper and lower limbs), it was possible to see, after 56 weeks, improvements in functional autonomy, mobility, and flexibility [34].…”
Section: Discussionsupporting
confidence: 86%
“…Evidence does consistently suggest that exercise leads to significant improvements in physical fitness, increased flexibility, agility, and strength [32,41,[45][46][47][48]. However, in our present work, physical fitness showed a decline in both exercise prescription groups.…”
Section: Discussioncontrasting
confidence: 73%
“…In regards to the measured outcomes, of the 26 articles included in the study, eighteen articles used DXA scanners [ 33 , 34 , 36 , 38 46 , 48 50 , 52 , 54 ] to determine whether muscle hypertrophy was evident or not after the intervention, four articles used a BIA [ 35 , 51 , 53 , 55 ], two articles used MRI [ 9 , 31 ] scans and two articles used USI [ 32 , 37 ]. It is important to note that these screening tools were used to measure different regions of the body which had been exposed to the RT.…”
Section: Resultsmentioning
confidence: 99%
“…Of the different body regions exposed to RT, 23 studies implemented full-body RT [32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53][54][55], and 3 implemented lower body RT [9, 31,42]. Thus, only the areas of the body which underwent the RT intervention have been examined by the afore mentioned screening tools.…”
Section: Search Outcomesmentioning
confidence: 99%